2016
DOI: 10.1007/s10163-016-0523-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of concrete production with solid residues obtained from fluidized-bed incineration of MSW-derived solid recovered fuel (SRF)

Abstract: The aim of this work was to evaluate the use of solid residues derived from municipal solid waste-derived solid recovered fuel incinerated in a circulating fluidized-bed boiler for concrete production. The concrete mixtures casted by partially replacing the natural aggregates with bottom ash (27 %) and exhausted sand (13 %), according to the European standards for concrete, may be classified in the C16/20 class. The leaching tests performed on monolithic concrete samples showed that the concentrations measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Leaching test results conducted by Keulen et al [76] complied with standard reference: only salts release, mainly Cl and Br, increased at high replacement levels. Collivignarelli et al [58] confirmed the environmental compatibility of MSWI ash aggregates in concrete by means of leaching tests, achieving a lower release than sand for chlorine, chromium, and bromine. The pollutants mobility and concentration have been highly influenced by the pH [77].…”
Section: Environmental Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Leaching test results conducted by Keulen et al [76] complied with standard reference: only salts release, mainly Cl and Br, increased at high replacement levels. Collivignarelli et al [58] confirmed the environmental compatibility of MSWI ash aggregates in concrete by means of leaching tests, achieving a lower release than sand for chlorine, chromium, and bromine. The pollutants mobility and concentration have been highly influenced by the pH [77].…”
Section: Environmental Propertiesmentioning
confidence: 94%
“…However, MSWI ash concrete have shown a higher shrinkage, creep, and chloride-diffusion coefficients [69]. Collivignarelli et al [58] underlined the critical points for the environmental compatibility of aggregates based on MSWI ash: (i) the high amount of heavy metals, which affects durability; (ii) the high content of chloride, which enhances the steel corrosion. The problems concerning expansion and cracking are due to the development of gaseous hydrogen caused by the corrosion of metals in an alkaline environment [70].…”
Section: Residues From Waste Treatmentmentioning
confidence: 99%
“…According to the Ministerial Decree 2006/186 [25], the unwashed BA from mass-burning kiln (MSWI-A) and the residues from fluidized bed reactor (MSWI-B), especially the exhausted SAND, were not suitable for recovery in simplified procedures [23]. This behaviour could be explained, as said above, as a consequence of several recirculation of the sand in the burning kiln during the combustion.…”
Section: Release Of Pollutants From Residues and Concrete Mixturesmentioning
confidence: 99%
“…Following these data and goals to enhance application of the CE, the present review aims to analyse the state of the art in the potential application of agricultural industry residues both in building and environmental engineering fields. Unlike many other reviews and articles written about sustainable materials composed of renewable resources -both organic such as reeds (Asdrubali et al, 2015), banana bunch (Pappu et al, 2007), or inorganic such as incineration bottom ash (Collivignarelli et al, 2017a), and steel slag or foundry sand (Abbà et al, 2017) -this study focuses on natural materials at the end of their life cycle that can be reused in environmental engineering applications, mainly wastewater (WW) treatments, or as raw materials for insulation panels and boards. As the production of the waste materials is mainly located in the same farming countries, the present paper focuses on direct application of the residues suitable for the producing countries.…”
Section: Introductionmentioning
confidence: 99%